Subnational political regimes and formal economic regulation: Evidence from Russian regions. Issue 2 (15th March 2017) - Libman, Alexander
ABSTRACT: The paper contributes to the studies of effects of political regimes on public policies by looking at a previously unexplored aspect of this issue: the propensity of political regimes to create vast and extensive formal regulation. To study this topic, it applies subnational comparative method and uses a dataset of subnational regions of Russia, which provides a unique opportunity for a large-N investigation of the research question because of substantial variation of regional political regimes and regulatory environments and because of availability of a proxy for comparing the use of formal regulation across regions. The paper shows that more competitive regimes are more likely to expand the formal law than less competitive ones; however, the implications of this expansion of formal law for the economy are ambiguous.